Mixed Logit with Repeated Choices: Households' Choices of Appliance Efficiency Level - Revelt, David; Train, Kenneth (The Review of Economics and Statistics, 1998)
Mixed logit models, also called random-parameters or error-components logit, are a generalization of standard logit that do not exhibit the restrictive “independence from irrelevant alternatives” property and explicitly account for correlations in unobserved utility over repeated choices by each customer. Mixed logits are estimated for households' choices of appliances under utility-sponsored programs that offer rebates or loans on high-efficiency appliances.